2018
DOI: 10.1080/2162402x.2018.1474317
|View full text |Cite
|
Sign up to set email alerts
|

Tumor stroma-infiltrating mast cells predict prognosis and adjuvant chemotherapeutic benefits in patients with muscle invasive bladder cancer

Abstract: Which subgroups patients with muscle-invasive bladder cancer (MIBC) could benefit most from adjuvant chemotherapy (ACT) is blurred. Here we tried to stratify MIBC patients with tumor infiltrating mast cells (TIMs), explore the prognostic and predictive value of TIMs, and provide possible cellular explanations. We selected 259 MIBC patients who underwent radical cystectomy from two independent clinical centers between 2002 and 2014. TIMs were evaluated and prognostic and predictive value was assessed. The CIBER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 38 publications
2
72
0
Order By: Relevance
“…Thus, identifying crucial subsets to deflect immune responses may be the key to “unlock” the immune evasion. Intriguingly, we found that high IL22 + cells infiltration marked immunosuppressive contexture with increased pro‐tumor cells (Tregs, Th2, M2 and mast cells), which agreed with the defined Immunotype B MIBC with worse clinical outcomes in our previous research . Furthermore, we observed IL10 + and TGF‐β + cells were enriched in tumors with high IL22 + cells infiltration, implying these increased pro‐tumor cells determined immunoevasive subtype MIBC by secreting IL10 and TGF‐β.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, identifying crucial subsets to deflect immune responses may be the key to “unlock” the immune evasion. Intriguingly, we found that high IL22 + cells infiltration marked immunosuppressive contexture with increased pro‐tumor cells (Tregs, Th2, M2 and mast cells), which agreed with the defined Immunotype B MIBC with worse clinical outcomes in our previous research . Furthermore, we observed IL10 + and TGF‐β + cells were enriched in tumors with high IL22 + cells infiltration, implying these increased pro‐tumor cells determined immunoevasive subtype MIBC by secreting IL10 and TGF‐β.…”
Section: Discussionsupporting
confidence: 90%
“…Recent findings indicated that the efficacy of chemotherapy and ICIs inextricably linked to the tumor microenvironment (TME) and tumor‐infiltrating immune cells . Our previous studies have revealed immune cells infiltration patterns comprised with neutrophils, CD8 + T cells, NK cells, Treg cells, macrophages, mast cells and B cells could affect immune contexture and ACT responsiveness in MIBC . Immunoregulatory cytokines, such as IL10 and IL17 (our unpublished research), may serve critical roles in therapeutic effectiveness .…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…BLCA is an immunosensitive tumor which is infiltrated by tumor-infiltrating immune cells (TIICs) including T cells, macrophages, dendritic cells, neutrophils and mast cells [7][8][9]. Studies have shown that the tumor microenvironment affects the gene expression of tumor tissues and the patient outcome, and therefore, has a diagnostic and prognostic value for BLCA [10][11][12]. TIICs, which are main components of tumor microenvironment, have been reported closely related to the effectiveness of targeted drugs and clinical outcomes.…”
Section: Ivyspringmentioning
confidence: 99%